2022
DOI: 10.1007/s00737-021-01201-9
|View full text |Cite
|
Sign up to set email alerts
|

Burden of severe maternal peripartum mental disorders in low- and middle-income countries: a systematic review

Abstract: Peripartum severe mental disorders (PSMDs) encompass schizophrenia, affective psychosis, and psychotic and non-psychotic forms of bipolar disorders. PSMDs are well documented in high-income countries. However, much less is known about the prevalence of PSMDs in low- and middle-income countries (LMICs). The aim was to review the available literature systematically and estimate the prevalence of PSMDs among women in LMICs. We searched the Ovid MEDLINE, Embase, PsycINFO, CINAHL and Maternity and Infant Care datab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“… 64 A separate systematic review (five studies in LMICs) reported a cumulative incidence of postpartum psychosis of 1·1 per 1000 births, and the prevalence between studies ranged from 1·1 to 16·7 per 1000 births. 65 Anxiety disorders A systematic review reported that the pooled prevalence of postpartum anxiety disorder was 16% (95% CI 13·5–18·9) and of self-reported anxiety symptoms was 24·4% (16·2–33·7). 66 A separate systematic review reported the pooled prevalence of postpartum anxiety disorder was 9·6% (3·4–15·9) at 5–12 weeks postpartum, 9·9% (6·1–13·8) at 1–24 weeks postpartum, and 9·3% (5·5–13·1) at over 24 weeks postpartum.…”
Section: The Global Burden Of Neglected Medium-term and Long-term Con...mentioning
confidence: 99%
“… 64 A separate systematic review (five studies in LMICs) reported a cumulative incidence of postpartum psychosis of 1·1 per 1000 births, and the prevalence between studies ranged from 1·1 to 16·7 per 1000 births. 65 Anxiety disorders A systematic review reported that the pooled prevalence of postpartum anxiety disorder was 16% (95% CI 13·5–18·9) and of self-reported anxiety symptoms was 24·4% (16·2–33·7). 66 A separate systematic review reported the pooled prevalence of postpartum anxiety disorder was 9·6% (3·4–15·9) at 5–12 weeks postpartum, 9·9% (6·1–13·8) at 1–24 weeks postpartum, and 9·3% (5·5–13·1) at over 24 weeks postpartum.…”
Section: The Global Burden Of Neglected Medium-term and Long-term Con...mentioning
confidence: 99%
“…3 In low and middle-income countries, the cumulative incidence of peripartum severe mental disorders ranged from 1.1 to 16.7 per 1000 births. 5 The relationship between marriage and mental illness is complex. Marriages in India are usually arranged by parents and are influenced by several factors such as astrological compatibility, caste regulation, geographic proximity, socio-economic equivalency, prescribed values, and expectations of dowry, it is not just a tie of two human beings but establishes as a constellation of many other relationships surrounding the couples.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of evidence-based interventions for reduction of common perinatal mental disorders is essential for women who are often suffering in silence (McNab et al, 2022). They should be integrated into peripartum health care (Kalra et al, 2022), with group care models such as Centering Pregnancy, which has shown to be an effective approach making an important difference. Midwife caseload models are proving effective globally, particularly for childbearing and childrearing women living in LMICs (Michel-Schuldt et al, 2020).…”
mentioning
confidence: 99%
“…Identification of and attention to social determinants of health in peripartum women is critical. Social determinants of health include cultural and social context, race and ethnicity, lack of social support, financial and nutritional insecurity, substance use, gender inequities, intimate partner violence, and a paucity of appropriate health care resources (Kalra et al, 2022; McCarthy et al, 2021; McNab et al, 2022; Ruyak & Kivlighan, 2021).…”
mentioning
confidence: 99%
See 1 more Smart Citation